Improving the ischemia-reperfusion injury in vascularized composite allotransplantation: Clinical experience and experimental implications - He, Jiqiang; Khan, Umar Zeb; Qing, Liming; Wu, Panfeng; Tang, Juyu (Frontiers in Immunology, 2022)
Long-time ischemia worsening transplant outcomes in vascularized composite allotransplantation (VCA) is often neglected. Ischemia-reperfusion injury (IRI) is an inevitable event that follows reperfusion after a period of cold static storage. The pathophysiological mechanism activates local inflammation, which is a barrier to allograft long-term immune tolerance. The previous publications have not clearly described the relationship between the tissue damage and ischemia time, nor the rejection grade. In this review, we found that the rejection episodes and rejection grade are usually related to the ischemia time, both in clinical and experimental aspects. Moreover, we summarized the potential therapeutic measures to mitigate the ischemia-reperfusion injury. Compare to static preservation, machine perfusion is a promising method that can keep VCA tissue viability and extend preservation time, which is especially beneficial for the expansion of the donor pool and better MHC-matching.